Podcast as Interactive Learning Media in Indonesian Language Learning in Elementary Schools: Podcast Sebagai Media Pembelajaran Interaktif dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Prawoto, Agung T (Universitas Muhammadiyah Sidoarjo, 2023)
Indonesian is a medium for communication and bonding to national unity. The many problems in understanding Indonesian and the obstacles to learning Indonesian for the general public, especially for students, is a crucial matter to find a solution to. Podcast interactive media is one of the learning media that is expected to be a solution to support the Indonesian language learning process. This is supported by the ADDIE method, which emphasizes strengthening substances such as Analysis, Design, Development, Implementation, and Evaluation. Thus, it is expected to be able to improve language skills and interest in learning Indonesian for students.